Awareness Regarding Diabetes Mellitus among General Population of Banepa Municipality - Manandhar, S.; Buddhacharya, M.; Maharjan, S. (Kathmandu University Medical Journal, 2021)
Background Diabetes is a silent disease and many people with diabetes may become aware of it only after life-threatening complications. The presence of knowledge of diabetes could contribute in early diagnosis and minimize the occurrence of complications. Hence, healthcare and public policy makers are putting extensive efforts to aware them on diabetes. Objective To assess the level of diabetes knowledge and its risk among the general public of Banepa municipality. Method A Cross sectional study was conducted to assess the awareness about diabetes among the general public of Banepa municipality. During the period of November 2019 to January 2020, 273 respondents of Banepa municipality were included with informed consent. Data was collected using a pre-tested structured questionnaire through one-to-one interviews. Indian Diabetes risk score (IDRS) was used to identify the risk of diabetes among them that consists of four elements i.e. age, abdominal obesity, physical activity, and family history. Data entry and analysis was done using SPSS version 20. Result It was found that 61.9% had a higher level of knowledge of diabetes. IDRS score shows more than half percent (53.5%) of respondents were in high risk, 39.2% were in medium risk and 7.3% were in low risk. Conclusion This study implies that there was good knowledge about diabetes among people. However, the majority of them are at risk for developing diabetes in future which may be due to lack of practical implication of knowledge. It reflects the necessity to educate and reinforce the public regarding prevention of diabetes which further postpones its complications.